2015
DOI: 10.1002/biot.201400780
|View full text |Cite
|
Sign up to set email alerts
|

Over‐expression of ICE2 stabilizes cytochrome P450 reductase in Saccharomyces cerevisiae and Pichia pastoris

Abstract: Membrane-anchored cytochrome P450 enzymes (CYPs) are a versatile and interesting class of enzymes for industrial applications, as they are capable of regio- and stereoselectively hydroxylating hydrophobic molecules. However, CYP activity requires sufficient levels of suitable cytochrome P450 reductases (CPRs) for regeneration of catalytic capacity, which is a bottleneck in many industrial applications. Searching for positive effectors of membrane-anchored CYP/CPR function, we transformed and screened selected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 68 publications
1
33
0
Order By: Relevance
“…Further studies are needed to better understand underlying structural and biochemical determinants such as enzyme kinetic parameters. Other than the fusion design, the formation of heterotrimeric protein‐mediated complex comprised of class I CYP and its redox partners and the stabilization of hetereologously expressed redox partners might be applied in creating efficient TxtE‐based nitration biocatalysts.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies are needed to better understand underlying structural and biochemical determinants such as enzyme kinetic parameters. Other than the fusion design, the formation of heterotrimeric protein‐mediated complex comprised of class I CYP and its redox partners and the stabilization of hetereologously expressed redox partners might be applied in creating efficient TxtE‐based nitration biocatalysts.…”
Section: Discussionmentioning
confidence: 99%
“…Usually raffinose is added to minimal medium containing galactose for protein expression induction. 27 As an organic compound, glycerol assimilation can occur in the presence of galactose in yeast. Earlier work indicated that the glycerol or raffinose addition might be favor to noscapine biosynthesis.…”
Section: De Novo Production Of (+)-Valencene Related Terpenoids Throumentioning
confidence: 99%
“…Production of trans -nootkatol was further improved by overexpression of the native yeast type III membrane associate protein Ice2p [ 77 ]. Introduction of this genetic modification into recombinant strain engineered earlier to produce (+)-valencene via expression of premnaspirodiene oxygenase (HPO; CYP) from Hyoscyamus muticus and cytochrome P450 from A. thaliana ( At CPR) [ 64 ], resulted in stabilizing the levels and enzymatic activity of the latter heterologous enzyme.…”
Section: Heterologous Compounds Derived From Intermediates Of the mentioning
confidence: 99%